(untitled) (Hekima Review, 2016)
Every wound leaves a scar and every scar speaks of a history; it reminds that you are alive (Buri gikomere gisiga inkovu, kandi buri nkovu ivuga amateka, ikwibutsa ko uriho). The wisdom of this Rwandan saying has never been as needed as it is today, particularly with regards to the tragic history of Rwanda that led to the genocide perpetrated against the Tutsi and the scars it has left to the whole country. Since a family that does not remember vanishes (umuryango utibuka urazima), I here argue that memory transcends national boundaries; it is a theological imperative. There is sufficient evidence to suggest that for Rwanda’s future, memory is of decisive significance. Rwandese must not allow themselves to be talked out of unreconciled memories even by theology, but rather they “must have faith with them and with them speak about God.”